The Implementation of Talent Management Practices in U.A.E. Organizations - AL AWADHI, KHALID MOHD AMIN KAMALI (2018)
In contemporary business, talented individuals are considered as one of the most important assets and the key to the success and continuity of any organization. Companies worldwide from many different industries have adopted numerous practices/programs to attract, promote and retain talented employees. These practices/programs are often referred to as “Talent Management”. In general, the main goal of any Talent Management at any organization is to ensure having the right talented people for the right positions, all the time. The challenge, as evident from many studies, is that talents are not easy to find and/or not easy to maintain. The main purpose of this research was to investigate, through primary and secondary data, the views and perceptions on the topic of Talent Management, and also the challenges associated with it in general. Based on that, the aim was to develop a comprehensive conceptual framework for the Talent Management process/model that can be applied in different organizations. In the first stage of this dissertation, after the review of the literature on the subject, an initial conceptual framework was developed. The framework comprised of eight stages; stage one is the alignment of Talent Management objectives with business goals. Stage two is the alignment of Talent Management programs with the Human Resources function. Stage three is the identification of pivotal and key positions in the organization. Stage four is creating a talent pool that includes talented individuals from internal and external sources. Stage five is about the enhancement of talents capabilities and competencies for current and future roles. Stage six is taking great measures to motivate and engage talents. Stage seven is the output from the process – having right motivated and competent talents all the time. The final stage, stage eight is the outcome – as a result of the previous stages, organizations will have a sustainable competitive advantage, better performance, and more profits. In the second stage of this dissertation, the aim was to study how UAE organizations practice and implement Talent Management. Interviews were conducted with five organizations within the UAE that are implementing Talent Management programs. Based on the findings from the interviews and the discussion in this dissertation, it was concluded that, if considered, these three factors will add great value to Talent Management processes. The factors are; a) Communication, b) Knowing the needs and ambitions of the talents, and finally, c) The Readiness of Managers. Accordingly, the conceptual framework was modified to include those factors.